CORRELATION BETWEEN ANEMIA AND THE INCIDENCE OF DYSMENORRHEA IN ADOLESCENT GIRLS - Hasnia, Faizah; Rize Budi Amalia; Lestari Sudaryanti; Annas, Jimmy Yanuar (UNIVERSITAS AIRLANGGA, 2024)
Abstract Background: Anemia, characterized by a low number of red blood cells or hemoglobin levels, can be one of the factors that play a role in the occurrence of dysmenorrhea during menstruation. Hemoglobin is unable to fulfill its function of transporting adequate amounts of oxygen to peripheral tissues. This causes women who experience anemia to experience frequent dysmenorrhea. The purpose of this study was to determine the relationship between anemia and the incidence of dysmenorrhea. Methods: This research method was observational analytic with cross sectional research design. The sample in this study were 132 adolescent girls in grades 11 and 12 at Mambaus Sholihin Islamic Boarding School, Gresik District, East Java. Data analysis in this study was chi square test. Results: The results showed that 34.1% were anemic and 65.9% were not anemic. Adolescents who experienced dysmenorrhea were 91.7% and 8.3% did not experience dysmenorrhea. Statistical tests to analyze the relationship between anemia and the incidence of dysmenorrhea using chisquare obtained pvalue = 0.01. Conclusion: There is a relationship between anemia and the incidence of dysmenorrhea at Mambaus Sholihin Islamic Boarding School.